A novel gastric ulcer model in rats using filter paper with acetic acid - Siyuan Dong; Xudong Wang; Yixin Liu; Lu Qiao; Qiong Xue; Yixin Zhou; Zhao Xu; Qun Chen; Chen Chen; Na Liu; Jinhai Wang (PLoS ONE, 2025)
Gastric ulcer animal models are essential for research, but conventional acetic acid-based methods are limited by technical complexity, prolonged modeling duration, and poor applicability for solid anti-ulcer drug testing. This study described a novel and simplified method for inducing gastric ulcers in rats using filter paper imbued with acetic acid. The method provided consistent ulcer formation with uniform size and shape, allowing for targeted drug efficacy testing. Results indicated that the 75% acetic acid concentration yielded the most clinically relevant gastric ulcer model, completed ulcer forming within a day and healing visible after seven days. In conclusion, this model closely replicates human gastric ulcers and is well-suited for preclinical testing of anti-ulcer drugs.